CRM Practices in the Telecom Sector of Punjab - Singh , Harjot; Singh , Raghbir (Gyan Management Journal, 2013)
The paper investigates the CRM practices of nine mobile phone service providers, currently operational in the Punjab Telecom Circle, through a primary study. 108 executives, twelve from each service provider, representing five telecom districts, have been selected on the basis of convenience sampling. The paper analyzes the type of services offered by the service providers, extent and duration of CRM practices, objectives of CRM, level of person heading the CRM function, frequency of interaction of executives with consumers, modes of communication used for the interaction and the perception of executives regarding the practices causing disturbance to consumers.